Case Report: Massive emphysematous pyelonephritis with short-term relapse - Jiang, Tingfei; Meng, Letian; Chen, Tong; Yang, Jie; Li, Xiao; Yao, Liangyu; Zhong, Da; Song, Ninghong (Frontiers in Medicine, 2025)
BackgroundEmphysematous pyelonephritis (EPN) is a rare but aggressive infectious disease that lacks specificity in its early stages and tends to progress to life-threatening septic shock in a short period of time. Its diagnosis is based on imaging tests, and treatment requires a combination of staging and risk factors.Case presentationWe report a case of emphysematous pyelonephritis in a patient with massive emphysema of the left kidney (the longest diameter up to 51 mm) on CT. After multidisciplinary consultation, the patient underwent CT-guided percutaneous drainage combined with targeted antibiotic therapy, and was discharged from the hospital with improvement of the condition. However, relapse of symptoms occurred after 1 day of discharge from the hospital, prompting readmission. After an additional 7-day course of antibiotic therapy, the patient recovered completely with no recurrence during 1-month follow-up.ConclusionStaged diagnosis and individualized therapeutic measures are key to the prognosis of this disease. Despite advances in therapeutic techniques, the risk of relapse is still high, and a comprehensive assessment of infection control is recommended for discharge from the hospital, with intensive follow-up to improve the prognosis.